Rozwój wspólnot domowego Kościoła w Ewangelii Marka w świetle "Tractatus in Marci Evangelium" Hieronima ze Strydonu - Mateja, Leszek (Vox Patrum, 2019)
The article delineates the process of formation of the ecclesial structure, presented in the Gospel according to St. Mark, from the founding of the first ecclesial community based on the οἰκία of Saimon and Andrew (cf. Mk 1:29) to the first miracle of multiplication of the loaves and fish (cf. Mk 6:34-44) which took place during the meeting of similar communities founded in Galilee. The inspiration for such an interpretation of this part of the Gospel according to Mark came from the oldest preserved commentary to this Gospel, written by Jerome of Stridon. The author, commenting on the healing the blind man from Bethsaida (cf. Mk 8:22-26) showed “home” as a symbol of the Church and presented a method of interpretation the Scriptures which enable us to read the message of the Gospel according to Mark in this way.